Peningkatan Literasi Keuangan Melalui Edukasi Pengelolaan Uang Saku Pada Siswa SMA Sunan Giri Menganti Gresik: Increasing Financial Literacy Through Pocket Money Management Education in Sunan Giri Menganti Gresik High School Students - Akhirruddin, Anita; Wasti Reviandani (JURNAL PENGABDIAN MANAJEMEN, 2026)
Financial literacy is a fundamental skill that is essential for students to possess as a preparation for facing future economic challenges. Students’ low understanding of financial management can trigger consumptive behavior and inappropriate financial decision-making. This community service program aims to provide financial education for high school students and its role in shaping students who are wise in managing their finances at Sunan Giri Menganti Gresik High School. Lectures, discussions, and financial management applications are the methods used in this community service activity. The results of the activity show that financial education can improve students’ understanding of managing money, distinguishing between needs and wants, and fostering an attitude of financial discipline and responsibility. Therefore, financial education needs to be systematically integrated into learning activities and school culture.